A Prehistory of Western North America : The Impact of Uto-Aztecan Languages - Shaul, David Leedom (Book collections on Project MUSE., 2014)
This book offers a new approach to the use of linguistic data to reconstruct prehistory. The author shows how a well-studied language family-in this case Uto-Aztecan-can be used as an instrument for reconstructing prehistory.